Hyperphosphorylation amplifies UPF1 activity to resolve stalls in nonsense-mediated mRNA decay - Sébastien Durand (Nature Portfolio, 2016)
Gene expression is regulated by a range of mechanisms, including post-translational modifications such as phosphorylation. Here the authors present evidence for a feedback mechanism whereby hyperphosphorylation of UPF1 in response to delays in nonsense-mediated decay enhances recruitment of mRNA decay machinery.